PENDIDIKAN DIABETES DI RUMAH SAKIT - Asri Prabawani Martan; Eka Ratnawati (Jurnal Kesehatan, 2021)
Introduction: Diabetes mellitus is a chronic disease that may cause further complications if it is not appropriately controlled. Diabetes education is needed so that diabetic patients can apply knowledge, and practical skills learned to manage their life with diabetes. Hospitalized diabetic patients need basic information about diabetes on their first admission to help them to better manage their diabetes at home. Diabetes education can also reduce length of hospitalization, limit readmissions and reduce the various complications associated with the disease. Methods: This research is an exploratory descriptive study that investigated what information that diabetic patient received on their first admission and who provided the education. Data were gathered via means of a semi structured interview. A convenience sample of eleven diabetic patients that have been hospitalized more than once were interviewed and the collected data were analyzed using thematic analysis. Results: The main themes that emerged from the data were medication, diet, blood glucose, skin integrity and life style. The interviews revealed that collaboration between nurse, dietician and doctor was the most common group of health practitioners who provided diabetes education during their first admission. The participants stated that the information was given at the time of discharge, and this information helped them manage their diabetes at home, although in some cases the information provided was not comprehensive. Conclusion: Nurse as an educator should be able to transfer their knowledge to patients, and have more chances to give health education to patients. Hospital should concern of nurse staffing because it can affect patient safety and quality of care. Institute and health practitioner should also collaborate in diabetes education and develop tools and program that effective for diabetes patients and help them to better manage their diabetes at home.